A CASE OF GRAVES’ DISEASE WITH SEVERE HYPERCALCAEMIA - Ng, Wei Wei (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION Mild to moderate hypercalcemia is seen in up to 20 percent of thyrotoxic patients. However, thyroid hormone-mediated severe hypercalcemia is rare. We report a case of Graves disease-induced symptomatic severe hypercalcemia. CASE A 25-year-old male presented with a three-week duration of abdominal pain, vomiting and constipation. He also complained of palpitations for one month and weight loss of 40 kilos within a year. Clinical examination revealed a temperature of 37.2°C, blood pressure of 120/72 mmHg and pulse rate of 140 beats per minute. He had fine tremors, exophthalmos and diffuse goiter with a thyroid bruit. Initial investigations showed significantly elevated free T4 of >64.35 pmol/L (9-19) with suppressed thyroid-stimulating hormone (TSH) of <0.008 μIU/mL (0.4-4.2). He had severe hypercalcemia with a serum calcium level of 3.97 mmol/L and a low serum intact PTH of 1.09 pmol/L (1.59-7.24). Serum phosphate, magnesium, creatinine and alkaline phosphatase were normal. TSH receptor antibody was raised at >40 IU/L (0-1.75) with normal anti-thyroid globulin and anti-thyroid peroxidase antibody. Neck ultrasound showed diffuse thyroiditis with increased vascularity in the thyroid gland. Tumour markers (CA19-9, CEA, AFP, PSA) were all normal. The skeletal survey revealed no lytic lesions. He was treated as a case of impending thyroid storm. Diagnosis of hyperthyroidism-induced hypercalcemia was made after excluding other common causes of hypercalcemia. He was started on propylthiouracil, propranolol, Lugol’s iodine and steroids. An intravenous saline infusion was started for hypercalcaemia without calcitonin or bisphosphonate. His serum calcium levels progressively declined and hypercalcemia-related symptoms resolved. He was discharged on day 8 of hospitalization with a normal calcium level of 2.5 mmol/L and fT4 of 40 pmol/L. CONCLUSION Hyperthyroidism is a potential cause of severe hypercalcemia. The treatment of hyperthyroidism may cause normalization of serum calcium levels as observed in this case.